Genetic counselors, patients', and carers' views on an Australian clinical genetics service information system. Issue 5 (18th April 2021) - Speechly, Catherine; Stenhouse, Rachael; Berman, Yemima; Barlow‐Stewart, Kristine; Fleming, Jane; Petrie, Dianne; Culling, Bronwyn
Abstract: The Genetic Information System (GIS) is an Australian database of family genetic information. This health information technology system has been used by all 31 publicly operated clinical genetics services across New South Wales (NSW) and the Australian Capital Territory (ACT) for over a decade. As these services are separated geographically, the linkage engendered by the GIS facilitates the services to operate as a virtual state‐wide service. This study aimed to explore the views of genetic counselors, patients, and carers on the use and storage of family genetic information in the GIS. Data were collected using audio‐recorded semi‐structured telephone interviews with genetic counselors experienced with using the GIS and focus groups with past patients/carers of the services. Using thematic analysis, four themes were identified from genetic counselor participant interviews ( n = 12): (a) Shared information is valuable; (b) inconsistent data entry provides a challenge; (c) perceived need for the GIS to be current and integrated with other health systems; and (d) future challenges and strategies for the GIS. Three themes were identified following three focus groups with consumer participants ( n = 14): (a) access to family genetic information provides a 'clearer picture'; (b) support, but caution, concerning use of information for relatives' health care; and (c) stewardship of family information. Genetic counselors and consumers identified similar advantages and privacy concerns regarding the sharing of family genetic information and all participants wanted patients/carers to be better informed about the GIS early in the genetic counseling process. Consumers were reassured by genetics health professionals' stewardship of their information, but surprised the GIS was not available nationally or for private geneticists or certain non‐genetic specialists. These findings may inform further development of the GIS and other clinical genetic databases and lead to increased patient/carer knowledge through education and resource development.